2015
DOI: 10.7554/elife.07464
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modelling, Bayesian inference, and new in vivo measurements elucidate the debated mtDNA bottleneck mechanism

Abstract: Dangerous damage to mitochondrial DNA (mtDNA) can be ameliorated during mammalian development through a highly debated mechanism called the mtDNA bottleneck. Uncertainty surrounding this process limits our ability to address inherited mtDNA diseases. We produce a new, physically motivated, generalisable theoretical model for mtDNA populations during development, allowing the first statistical comparison of proposed bottleneck mechanisms. Using approximate Bayesian computation and mouse data, we find most stati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
193
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(213 citation statements)
references
References 76 publications
15
193
0
Order By: Relevance
“…This is concordant with a recent analysis of the time-evolution of heteroplasmy variance in mouse oocytes, which concluded that the actual minimal bottleneck size is difficult to determine and may have only limited impact on overall heteroplasmy dynamics during oogenesis (Johnston et al, 2015). However, our estimates of the EBS (median 24.5, 95% CI: 11.6-35.1) are similar to other recent estimates of the oogenic bottleneck size, including an estimate of 32.3 in a previous analysis of the data used in this study (Rebolledo-Jaramillo et al, 2014), and a previous estimate of 9 in Li et al (2016).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This is concordant with a recent analysis of the time-evolution of heteroplasmy variance in mouse oocytes, which concluded that the actual minimal bottleneck size is difficult to determine and may have only limited impact on overall heteroplasmy dynamics during oogenesis (Johnston et al, 2015). However, our estimates of the EBS (median 24.5, 95% CI: 11.6-35.1) are similar to other recent estimates of the oogenic bottleneck size, including an estimate of 32.3 in a previous analysis of the data used in this study (Rebolledo-Jaramillo et al, 2014), and a previous estimate of 9 in Li et al (2016).…”
Section: Discussionsupporting
confidence: 77%
“…There has been considerable debate about whether the mechanism of this bottleneck involves an actual decrease in the number of mitochondrial genome copies versus co-segregation of genetically homogeneous groups of mitochondrial DNA (e.g., Jenuth et al, 1996;Cao et al, 2007;Cree et al, 2008;Wai et al, 2008;Carling et al, 2011). Nevertheless, in order to better predict the change in heteroplasmy frequencies between generations, previous studies have sought to infer the size of the oogenic bottleneck, either through direct observation (in mice) of the number of mitochondrial DNA genome copies (Cree et al, 2008;Cao et al, 2007), or through indirect measurement, making statistical conclusions about the bottleneck size based on observed frequency changes between generations (Johnston et al, 2015;Rebolledo-Jaramillo et al, 2014;Millar et al, 2008;Hendy et al, 2009;Li et al, 2016). Recently, Johnston et al (2015) have proposed a statistical framework that combines direct observations of mtDNA copy number with genetic variance in order to make inferences about the dynamics of the oogenic bottleneck.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations